Empire of light [videorecording (DVD)] - Mendes, Sam; Colman, Olivia; Ward, Micheal, 1995-; Brooke, Tom, 1978-; Moodie, Tanya; Onslow, Hannah; Clarke, Crystal (Actor); Jones, Toby, 1966-; Firth, Colin, 1960- (20th Century Studios ; Searchlight Pictures, 2023)
A drama about the power of human connection during turbulent times, set in an English coastal town in the early 1980s.